Phytochemical Profiles and Biological Activities of Plant Extracts from Aromatic Plants Cultivated in Cyprus - Chrysargyris, Antonios; Petrovic, Jovana D; Tomou, Ekaterina Michaela; Kyriakou, Kalia; Xylia, Panayiota; Kotsoni, Andria; Gkretsi, Vasiliki; Miltiadous, Panagiota; Skaltsa, Helen; Soković, Marina D.; Tzortzakis, Nikos G. (My University, 2024)
Medicinal and aromatic plants' properties, still an interesting research area, are attributed to the presence of various specialized products that possess important pharmacological activities. In the present study, six medicinal/aromatic plants (Sideritis cypria, Origanum dubium, Melissa officinalis, Mentha piperita, Thymus capitatus, and Salvia fruticosa) were evaluated for their phytochemical and nutritive composition, as well as their biological activities, including antioxidant, antimicrobial, and cytotoxic properties. The results obtained indicate that M. piperita was rich in proteins and minerals such as N and Mg, while S. cypria accumulated more K, Na, P, and Ca. The highest content of phenols and flavonoids was observed in M. piperita, followed by O. dubium and T. capitatus, which eventually influenced their high antioxidant capacity. NMR screening revealed the presence of (i) triterpenoids and hydroxycinnamic acid derivatives in M. officinalis; (ii) terpenoids, flavonoids, and phenolic acid derivatives in S. fruticosa; (iii) flavonoids and phenolic acid derivatives in M. piperita; (iv) phenolic monoterpenes in O. dubium and T. capitatus; and (v) terpenoids, flavones, and phenylethanoid glycosides in S. cypria. The results of the antimicrobial activity showed that the tested samples overall had quite good antimicrobial potential. High antibacterial activity was found in O. dubium and T. capitatus, while O. dubium and S. cypria exhibited great antifungal activities. The studied species also had an important effect on the viability of female-derived and colon cancer cells. In particular, in colon cancer cells, the extracts from T. capitatus, M. officinalis, M. piperita, and S. fruticosa exhibited a stronger effect on cell viability in the more metastatic cell line at significantly lower concentrations, indicating an important therapeutic potential in targeting highly metastatic tumors. This finding is worth further investigation. The present study unveiled interesting phytochemical profiles and biological properties of the six medicinal/aromatic plants, which should be further explored, contributing to green chemistry and the possible creation of natural health products for humans' health/nutrition and additives in cosmetics.
Keywords: NMR; Antimicrobial activity; Antioxidant activity; Chemical profiles; Cytotoxicity